Characterization of Alstroemeria species and cultivars using random amplified polymorphic DNA (RAPD) analysis - Picton, Deric D., author; Hughes, Harrison G., advisor; Ward, Sarah, committee member; Stushnoff, Cecil, committee member (Colorado State University. Libraries, 1997)
The characterization of Alstroemeria has not been effective through the use of conventional morphological markers. This is mainly due to the confused status of many of the species. Breeding of Alstroemeria has involved interspecific crosses as well as the use of mutagens and chromosome doubling for the creation of cultivars. Through the use of molecular techniques, in particular random amplified polymorphic DNA (RAPD) analysis, it is possible to uniquely characterize the species and cultivars. Fifteen species and hybrids along with 25 cultivars were examined using RAPD analysis. Four primers were eventually used for the analysis. All amplification products were separated using a 5% polyacrylamide gel and stained with silver nitrate for maximum differentiation of the fragments. The four primers yielded 73 amplification products which were polymorphic. When analysed using cluster analysis, all species and cultivars were uniquely characterized and putative parentages of many of the cultivars were determined.
Covers not scanned.
Keywords: Lilies -- Analysis; Genetic polymorphisms; DNA fingerprinting of plants